Medical robotic engineering selection based on square root neutrosophic normal interval-valued sets and their aggregated operators - Palanikumar, Murugan; Kausar, Nasreen; Garg, Harish; Iampan, Aiyared; Kadry, Seifedine; Sharaf, Mohamed (AMER INST MATHEMATICAL SCIENCES-AIMS, 2023)
We introduce the concepts of multiple attribute decision-making (MADM) using square root neutrosophic normal interval-valued sets (SRNSNIVS). The square root neutrosophic (SRNS), interval-valued NS, and neutrosophic normal interval-valued (NSNIV) sets are extensions of SRNSNIVS. A historical analysis of several aggregating operations is presented in this article. In this article, we discuss a novel idea for the square root NSNIV weighted averaging (SRNSNIVWA), NSNIV weighted geometric (SRNSNIVWG), generalized SRNSNIV weighted averaging (GSRNSNIVWA), and generalized SRNSNIV weighted geometric (GSRNSNIVWG). Examples are provided for the use of Euclidean distances and Hamming distances. Various algebraic operations will be applied to these sets in this communication. This results in more accurate models and is closed to an integer Delta. A medical robotics system is described as combining computer science and machine tool technology. There are five types of robotics such as Pharma robotics, Robotic-assisted biopsy, Antibacterial nano-materials, AI diagnostics, and AI epidemiology. A robotics system should be selected based on four criteria, including robot controller features, affordable off-line programming software, safety codes, and the manufacturer's experience and reputation. Using expert judgments and criteria, we will be able to decide which options are the most appropriate. Several of the proposed and current models are also compared in order to demonstrate the reliability and usefulness of the models under study. Additionally, the findings of the study are fascinating and intriguing.
Keywords: aggregating operators; decision making; generalized square root neutrosophic normal interval-valued weighted averaging; generalized square root neutrosophic normal interval-valued weighted geometric; DECISION-MAKING; FUZZY; TOPSIS; Mathematics